Gambaran Self-Compassion pada Individu yang Menjalin Long-Distance Relationship - Hayati, Salma; Marsha, Gladis Corinna; Fikrie (Flourishing Journal, 2025)
A long-distance relationship, also known as LDR, brings about various complex emotional challenges, such as feelings of loneliness, uncertainty, and limited physical interaction. This situation can increase the risk of stress and anxiety, especially during the uncertain period of emerging adulthood. Self-compassion, as the ability to accept oneself with kindness, becomes very important in helping individuals face these challenges without falling into excessive self-criticism or emotional isolation. This study aims to provide a comprehensive overview of self-compassion in individuals who are in long-distance relationships. The method used in this research is qualitative with a phenomenological design. Data collection uses interview and observation methods. This study employs purposive sampling as its sampling technique. The subjects in this study consist of two individuals who meet the criteria of young adults currently in a long-distance relationship. Both subjects demonstrate strong self-compassion in maintaining a long-distance relationship, reflected in their behaviours of self-kindness, common humanity, mindfulness, as well as openness and self-reflection in balancing personal needs and the relationship. AbstrakLong distance relationship atau bisa disebut LDR menimbulkan berbagai tantangan emosional yang kompleks, seperti rasa kesepian, ketidakpastian, dan terbatasnya interaksi secara fisik. Situasi ini dapat meningkatkan risiko stres dan kecemasan, terutama pada masa emerging adulthood yang penuh ketidakpastian. Self-compassion sebagai kemampuan untuk menerima diri sendiri dengan penuh kasih sayang, menjadi sangat penting untuk membantu individu menghadapi tantangan tersebut tanpa terpuruk dalam kritik diri berlebihan atau terisolasi emosional. Penelitian ini bertujuan untuk memberikan gambaran komprehensif mengenai self-compassion pada individu yang menjalani LDR. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan desain fenomenologi. Pengambilan data menggunakan metode wawancara dan observasi. Teknik pengambilan sampel pada penelitian ini menggunakan teknik purposive sampling. Subjek dalam penelitian ini terdiri dari dua orang dengan kriteria individu dewasa awal yang sedang menjalani long distance relationship. Kedua subjek menunjukkan self-compassion yang kuat dalam menjalani hubungan jarak jauh, tercermin dari perilaku self-kindness, common humanity, mindfulness, serta keterbukaan dan refleksi diri dalam menjaga keseimbangan kebutuhan pribadi dan hubungan.